Sosialisasi Alur Tugas Akhir Untuk Dosen dan Tenaga Kependidikan di Universitas Harapan Bangsa - Maya Ruhtiani; Puspita Lianti Putri; Slamet Slamet; Yuris Tri Naili (Jurnal Pengabdian Masyarakat - PIMAS, 2023)
The final project is a student's scientific writing that reflects the ability to carry out processes and patterns of scientific thinking through study or engineering activities and is accounted for through exams as a requirement for obtaining a bachelor's degree. Socialization activities for the final task flow were given to lecturers and educational staff at Harapan Bangsa University. The determination of participants for this socialization is an attempt to convey the importance of understanding the flow of the final task so that lecturers and educational staff can comply with the guidelines when carrying out guidance and direction to students. This socialization provides an understanding that the final project is a reference for students, lecturers, study programs, and faculties at Harapan Bangsa University, starting from the stages of identifying ideas, proposals, research, preparing reports, examinations, and assessments. The method used is direct outreach to lecturers and education staff at Harapan Bangsa University. Socialization activities aim to give lecturers and educational staff an understanding of the flow of the final project. The results of socialization have a positive impact. Namely, there is harmony between the final assignment guidelines and the final assignment flow carried out by lecturers and education staff which has an impact on the smooth running of the final assignment preparation process.